Bankruptcy Analysis with the Altman Z-Score Method Case Study on Ubamie Restaurant - Oktavia, Earlyne Nur; Majid, Nurkolish (PT FORMOSA CENDEKIA GLOBAL, 2023)
Financial statements are documents that present the revenues, costs, and net income or loss of a company over a period of time. This report is an important tool in financial analysis for company performance evaluation and strategic decision making. This journal examines the role of financial statement analysis through company cash flow as an effective tool in making business decisions engaged in the F&B sector, to be precise a case study of Ubamie restaurant. This research uses a quantitative descriptive method with a case study approach that includes analyzing historical data on the company's financial statements. This research aims to provide a better view of effective financial statement analysis methods to support proper decision making at various levels of the company or business. The results of this study can provide valuable insights for stakeholders, such as business owners, investors, and management, to take appropriate steps to improve financial health and reduce the risk of bankruptcy